An analog of double electromagnetically induced transparency with extremely high group indexes - Yang, An (2013)
An asymmetric metamaterial exhibiting an analog of double electromagnetically induced transparency (EIT) in the middle-infrared region is reported. The metamaterial consists of two-layered arrays of U-shaped rings embedded in a medium, with the lower layer rotated by 90◦. Our simulations demonstrate that both maximum group indexes are extremely high at the two EIT-like positions. The group index reaches about thrice the currently reported maximum value at the high-frequency EIT-like position. The transmittance at the two transparency positions also possesses extremely high Q factors, which is conducive to controlling the propagation of electromagnetic waves.